2015
DOI: 10.1007/s10803-014-2351-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices for Children, Youth, and Young Adults with Autism Spectrum Disorder: A Comprehensive Review

Abstract: The purpose of this study was to identify evidenced-based, focused intervention practices for children and youth with autism spectrum disorder. This study was an extension and elaboration of a previous evidence-based practice review reported by Odom et al. (Prev Sch Fail 54:275-282, 2010b, doi: 10.1080/10459881003785506 ). In the current study, a computer search initially yielded 29,105 articles, and the subsequent screening and evaluation process found 456 studies to meet inclusion and methodological criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
1,307
2
67

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,368 publications
(1,398 citation statements)
references
References 56 publications
22
1,307
2
67
Order By: Relevance
“…Underreporting of cultural factors in the field of ASD is, however, well documented (Broder-Fingert et al 2017;Kistner and Robbins 1986;National Autism Center 2015;Pierce et al 2014;West et al 2016;Wong et al , 2015. For instance, Pierce et al (2014) evaluated methodological practices for reporting ethnicity for study participants in ASD studies published in three autism-related academic journals.…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Underreporting of cultural factors in the field of ASD is, however, well documented (Broder-Fingert et al 2017;Kistner and Robbins 1986;National Autism Center 2015;Pierce et al 2014;West et al 2016;Wong et al , 2015. For instance, Pierce et al (2014) evaluated methodological practices for reporting ethnicity for study participants in ASD studies published in three autism-related academic journals.…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
“…It was also revealed that when ethnicity was reported, 54% of these studies did not include ethnicity or race variable into data analysis. The reviews of intervention research reporting on evidence-based practices (EBPs) for children and youth with ASD (National Autism Center 2015; Wong et al , 2015 also showed that most efficacy studies did not systematically include information on cultural demographics of their participants. More specifically, these studies did not describe ethnicity, nationality, or race of the participants other than White, Caucasian, or European-American (West et al 2016).…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
“…1 ABAbased interventions for ASD have typically focused on either (a) skill acquisition through core ABA strategies (eg, discrete trial training, 2 pivotal response training 3 ), often performed within a developmental framework (eg, Early Start Denver Model 4 ), or (b) treatment of clinically significant behavior. 5 Among ABA methods for treating problem behavior in ASDs, functional communication training (FCT) 6 is the most widely used, and previous research has demonstrated that FCT can effectively treat many types of behavior problems across a variety of settings.…”
mentioning
confidence: 99%
“…Fortunately, the emerging field of implementation science may provide the needed guidance for such a translational process (Fixsen, Blase, Metz, & Van Dyke, 2013), and professional development models for teachers and service providers working with children and youth with ASD have begun to adopt an implementation science approach (Odom, Cox, & Brock, 2013).All of this points to the fact that from science to practice is a clear challenge and furthermore an imperative next stride for the field (Wong et al,2014). One approach to improving services to students with ASD enrolled public school programs is through professional development.…”
Section: Resultsmentioning
confidence: 99%